Shifting focus from subtractive to additive technology in digital prosthodontics - Sai Kiran Koppolu; P S Manoharan (Wolters Kluwer Medknow Publications, 2022)
The advancements in digital technologies have found a widespread application in fabrication of dental restoration with adequate precision and accuracy. Digital methods which are commonly used for fabrication of prosthesis include subtractive methods such as milling and additive methods such as photomelting and photopolymerizing. Digitalization and accuracy are paving the way toward additive technology. The main purpose of this short communication is to mention the advantages, applications, and studies comparing additive and subtractive technology.